Endomárketing: Estrategia de innovación en las organizaciones el siglo XXI (2017)
Productivity, profitability and good organizational climate are the challenges that companies, regardless of their size, assume in this century. The permanent competitiveness has generated a tight business environment in the level of internal gear of the company is reflected in the positioning of the product or service that offers the same to the end customer. This is why managing to the interior of companies has taken on a role in generating innovative processes such as Endomarketing. This is a series of techniques directed and applied to the internal customers (employees) that create the permanent motivation towards the accomplishment of their daily tasks, the commitment and the end of the organization, to make the worker the first client, in the more faithful and The best reference that the final customer can find. This article proposes that Endomarketing is an effective strategy to improve organizational processes, internal customer satisfaction and business projection.